The biological role of omega subunit of cyanobacterial RNA polymerase - Kurkela, Juha (fi=Turun yliopisto|en=University of Turku|, 2020)
ABSTRACT Cyanobacteria are important primary producers performing oxygenic photosynthesis using CO2 or HCO3- as a carbon source. Active adjustment of gene expression according to environmental cues depends on the RNA polymerase (RNAP). The cyanobacterial RNAP core (α2ββ’γω) recruits one of regulatory σ factors to form an RNAP holoenzyme that recognizes the promoter sequence and initiates transcription. The RNAP core structure of cyanobacteria is unique due to splitting of β’ into γ and β’ subunits. The small ω subunit of RNAP, encoded by the rpoZ gene, has been found to be non-essential in many heterotrophic bacteria but has not been studied in cyanobacteria. To characterize the ω subunit, an inactivation strain (ΔrpoZ) was constructed in the cyanobacterial model organism Synechocystis sp. PCC 6803. The ω subunit was found to be non-essential in our standard growth conditions but essential in heat and in high CO2. The carbon concentrating mechanisms, carbon fixation and nitrogen acquisition genes were downregulated in ΔrpoZ in standard conditions, whereas other household genes including transcription and translation machinery genes expressed normally. Although ΔrpoZ grew well in standard conditions, light saturated photosynthetic activity was low and some photoprotective mechanisms were upregulated. The heat lethal phenotype of ΔrpoZ was accompanied with a highly abnormal transcriptome but high amounts of rRNA in ΔrpoZ indicated that the ω-less RNAP stayed active upon heat treatment. In high CO2, more stationary phase specific RNAP-SigC holoenzyme was formed in ΔrpoZ than in the control strain (CS), leading to downregulation of many photosynthesis, nitrogen acquisition and cell division genes. Thus, ΔrpoZ did not enhance photosynthesis, readjust C/N balance or produce enough cell wall components in high CO2, which eventually led to accumulation of glycogen and cell doublets, and to growth arrest. Spontaneously arised supressor mutants, ΔrpoZ-S1 and ΔrpoZ-S2, contained point mutations in the ssr1600 gene, which rescued acclimation to high CO2 and to heat. Due to L24S and G43V mutations of Ssr1600, the amount of the Ssr1600 protein was low in the suppressor mutants. Our results revealed that Ssr1600 functions as an anti-SigC antagonist. In the suppressor strains, similar low amount of RNAP-SigC holoenzyme is formed as in the CS, and cells acclimate to high CO2. KEYWORDS: Cyanobacteria, RNA polymerase, σ factor, ω subunit, high CO2, photosynthesis, cell division, Ssr1600, anti-σ factor antagonist, gene expression

TIIVISTELMÄ Syanobakteerit ovat tärkeitä perustuottajia, jotka käytttävät hiilen lähteenä joko CO2:ta tai HCO3-:ta. Syanobakteerit sopeutuvat ympäristön muutoksiin muuttamalla geenien ilmentymisestä vastaavan RNA-polymeraasin (RNAP) toimintaa. Syanobakteerien RNAP:n ytimeen (α2, β, β’, γ ja ω) kiinnittyy transkription aloitusta varten yksi säätelevistä σ-alayksiköistä ja RNAP-holoentsyymi tunnistaa geenin promoottorialueen ja käynnistää transkription. Tutkimusten mukaan ω on ainoa RNAP:n alayksikkö, joka ei ole välttämätön monilla heterotrofisilla bakteereilla. Syanobakteereissa ω-alayksikön tehtäviä ei ole kuitenkaan tutkittu ja tästä syystä rakennettiin kanta, joka ei tuota ω-alayksikköä (ΔrpoZ). Tavallisissa kasvatusolosuhteissa ΔrpoZ-kanta kasvoi hyvin, mutta kuumassa tai runsaassa CO2:ssa ΔrpoZ-kanta ei pystynyt kasvamaan. Solun perustoimintojen geeneistä hiilen keräämiseen ja sitomiseen sekä typen sisäänottoon osallistuvat geenit ilmenivät vähemmän ΔrpoZ-kannalla kuin villityypin kannalla (WT), mutta muut ylläpitogeenit ilmenivät normaalisti. Vaikka ΔrpoZ-kanta kasvoi tavallisissa olosuhteissa, sen maksimaalinen fotosynteesiteho oli pienempi kuin WT:llä ja soluihin kertyi valolta suojaavia yhdisteitä. Kuumassa RNAP pysyi toiminnallisena ilman ω-alayksikköä, mutta normaalia geenien ilmenemisen säätelyä ei tapahtunut. Kasvatettaessa soluja runsaassa CO2:ssa ΔrpoZ-soluihin muodostui paljon stationääriselle kasvuvaiheelle tyypillistä RNAP-SigC holoentsyymiä, jolloin monet fotosynteesistä, typen sisäänotosta ja solun jakautumisesta vastaavat geenit ilmenivät vähemmän kuin WT:llä. Geenien ilmentymisessä havaitut ongelmat estivät ΔrpoZ-kannan sopeutumisen lisääntyneeseen CO2:een: fotosynteesi ei tehostunut, typpi/hiili tasapaino ei säätynyt, jolloin glykogeeniä kertyi soluihin, solun jakautuminen pysähtyi ja lopulta ΔrpoZ-solut kuolivat. Itsenäisesti muuttuneista ΔrpoZ-kannoista (ΔrpoZ-S1 ja ΔrpoZ-S2) löydettiin genomisekvensoinnin avulla ssr1600-geenistä pistemutaatiot, jotka mahdollistivat ΔrpoZS1- ja ΔrpoZ-S2-kantojen kasvun korkeassa CO2:ssa. Mutaatioiden seurauksena Ssr1600-proteiini hävisi lähes kokonaan ΔrpoZ-S1- ja ΔrpoZ-S2-soluista. Tutkimalla ΔrpoZ-S-kantoja tarkemmin havaittiin, että Ssr1600-proteiini säätelee SigC:n sitoutumista RNAP:hen. ASIASANAT: Syanobakteerit, RNA-polymeraasi, σ-alayksikkö, ω-alayksikkö, hiilidioksidi, fotosynteesi, solunjakautuminen, Ssr1600